МИФ ҲӘМ ЕРТЕК ЖАНРЛАРЫ ӨЗГЕШЕЛИКЛЕРИНИҢ БАРЛЫҚ ТИЛ КӨРИНИСИНДЕГИ ТАЛҚЫСЫ - Усенова, В.Ж. (ILIM hám JÁMIYET, 2024)
This article presents an analysis of the genres of myth and fairy tale in the linguistic picture of the world. There are also many opinions expressed that the idea of myth and fairy tale are often similar, and the etymology of these terms is given as proof of these opinions. In addition, the main differences between myth and fairy tale are briefly outlined, and they are shown to be lexical units that verbalize conceptual, historical, structural and cultural features.